Analysis of Students Needs for Website-Based Computational Physics Teaching Materials on Linear and Nonlinear Equations - Wawan Kurniawan; Alrizal; M. Furqon; Yunita (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to analyze student needs for teaching materials needed in Computational Physics courses. This research is an quantitative research. The research subjects were physics education students in the 2021 batch of Jambi University who had contracted a computational physics course. The sample consisted of 25 students taken randomly. The research data were obtained from the results of the initial observation questionnaire and the desired teaching material needs analysis questionnaire. From the initial observation questionnaire, it can be concluded that 55.2% of students do not agree if they only use books as teaching materials, so it is necessary to develop teaching materials that are more practical and easy to understand. Based on the needs analysis of the development of teaching materials shows that 85.6% of students strongly agree if a teaching material is developed in the form of website development as teaching material for computational physics course supporters on linear and non-linear equations material.